BRAF mutations and BRAF mutation functional class have no negative impact on the clinical outcome of advanced NSCLC and associate with susceptibility to immunotherapy. (May 2021) - Wiesweg, Marcel; Preuß, Cedric; Roeper, Julia; Metzenmacher, Martin; Eberhardt, Wilfried; Stropiep, Ursula; Wedeken, Katrin; Reis, Henning; Herold, Thomas; Darwiche, Kaid; Aigner, Clemens; Stuschke, Martin; et al.
Abstract: Objective: BRAF mutations have been subtyped in three functional classes with different oncogenic modes of action. The clinical impact of BRAF mutational subtypes in non–small-cell lung cancer (NSCLC) remains to be defined. So far, ambiguous results were reported from analyses of heterogeneous patient cohorts. Methods: We studied patients with metastatic or recurrent NSCLC who were sequentially enrolled in precision oncology programs at two large German lung cancer centres from 2009 to 2019. The study period allowed evaluating the specific impact of BRAF V600E-targeting. Results: In a cohort of 72 patients, BRAF mutation subtyping revealed p.V600E mutations in 31 cases (43%), whereas 41 cases (57%) harboured 18 different BRAF mutational subtypes of functional classes II/III. Functionally relevant comutations were observed in 6.4% of class I, and 24.4% of class II/III BRAF mutations. Most patients were treated with chemotherapy. Targeted therapy was administered in 11 patients with a response rate of 72.7%. PD-1/PD-L1-immunotherapy was given in 14 patients with a response rate of 28.6%. Overall survival of patients with BRAF -mutated NSCLC was inferior (HR 1.38, p = 0.048) as compared to patients with BRAF wild-type cancers. Median time-to-treatment-failure with BRAF-targeting agents was shorter as compared to approved targeted therapy of other oncogenic drivers (HR 1.97, p = 0.05). Survival outcomes were not impacted by BRAF mutation subtype functional class. Conclusions: Patients with BRAF -mutated NSCLC have an inferior prognosis, which is not determined by BRAF mutation functional class. In contrast to NSCLC with other tractable driver mutations, BRAF -mutated NSCLC exhibit high susceptibility to immune checkpoint inhibitors. Highlights: PD-1/PD-L1 immunotherapy is effective in BRAF -mutant NSCLC. Patients with BRAF -mutated NSCLC have inferior overall survival. BRAF mutation functional class does not associate with clinical outcomes.